El surrealismo contado desde la perspectiva de Magritte - Mensa Torras, Marta (Mercurio Peruano, 2020)
If we asked Magritte in which movement his art might be included, he would surely answer us: Ceci n’est pas un surrealiste. With this expression he would like to explain to us the same thing that he expresses in the painting of the Betrayal of the images (1929): that the pipe painted on the canvas is not a pipe but the image of a pipe. However, he communicates it to us in an ironic and disconcerting way, in fact that is how his thinking and his painting are.